(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Five species of different pulses were screened in the laboratory for their susceptibility to the bean beetle Callosobruchus phaseoli using choice and non-choice tests.The bruchid showed various responses to the seeds with regard to oviposition, larval development and adult emergence. Considering all aspects the insect appears to be adapted to the seeds of Lablab purpureus Medik., but did not develop in the seeds of Phaseolus vulgaris L. (two varieties).